Angiographic Findings in ST-Segment Elevation Myocardial Infarction in Patients With Age Less Than 40 Years Admitted to a Tertiary Care Hospital - Qaid, Fazal; Adil, Muhammad; Sami, Haider; Khan, Shahzeb; Amin, Rooh ul; Khan, Asfandiyar; Iqbal, Muhammad Asif (Biological and Clinical Sciences Research Journal, 2025)
We sought to find trends about culprit vessels, lesion features, the existence of collateral circulation, and other noteworthy abnormalities by concentrating on a particular age group. The ultimate objective of this study was to improve knowledge of STEMI among younger individuals to guide therapeutic procedures and improve management outcomes for this susceptible group. Objective: To evaluate the angiographic findings in ST-segment elevation myocardial infarction in patients aged less than 40 years admitted to a tertiary care hospital. Methods: This cross-sectional study was carried out at the department of Cardiology, LRH, Peshawar, during the period (05-01-2025) till (05-04-2025). Male and female patients aged less than 40 years diagnosed with STEMI were enrolled. Angiography was performed, and findings were noted regarding culprit vessels, lesion characteristics, presence of thrombus, multi-vessel disease, coronary anomalies, and collateral circulation. Data were analyzed using SPSS v.26. Results: The mean age of the 385 participants was 30.50±5.28 years, with 198 (51.4%) patients aged over 30 years and 235 (61.0%) male. Single-vessel disease was the most frequently recorded in 262 patients (68.1%). Among the culprit vessels, the left anterior descending was most frequently observed in 191 patients (49.6%), followed by the right coronary artery in 110 patients (28.6%). 336 patients (87.3%) had an occlusive lesion, while thrombus was observed in 295 participants (76.6%). Conclusion: Male participants were more likely than females to be affected by STEMI under the age of 40 years. The most frequent angiographic diagnosis was single-vessel disease, and the most frequent culprit vessel was LAD.